Lactobacillus-derived extracellular vesicles counteract Aβ42-induced abnormal transcriptional changes through the upregulation of MeCP2 and Sirt1 and improve Aβ pathology in Tg-APP/PS1 mice - Hyejin Kwon; Eun-Hwa Lee; So-Young Park; Jin-Young Park; Jin-Hwan Hong; Eun-Kyung Kim; Tae-Seop Shin; Yoon-Keun Kim; Pyung-Lim Han (Experimental and Molecular Medicine, 2023)
Abstract Mounting evidence suggests that probiotics are beneficial for treating Alzheimer’s disease (AD). However, the mechanisms by which specific probiotics modify AD pathophysiology are not clearly understood. In this study, we investigated whether Lactobacillus paracasei-derived extracellular vesicles (Lpc-EV) can directly act on neuronal cells to modify amyloid-beta (Aβ)-induced transcriptional changes and Aβ pathology in the brains of Tg-APP/PS1 mice. Lpc-EV treatment in HT22 neuronal cells counteracts Aβ-induced downregulation of Brain-derived neurotrophic factor (Bdnf), Neurotrophin 3 (Nt3), Nt4/5, and TrkB receptor, and reverses Aβ-induced altered expression of diverse nuclear factors, including the downregulation of Methyl-CpG binding protein 2 (Mecp2) and Sirtuin 1 (Sirt1). Systematic siRNA-mediated knockdown experiments indicate that the upregulation of Bdnf, Nt3, Nt4/5, and TrkB by Lpc-EV is mediated via multiple epigenetic factors whose activation converges on Mecp2 and Sirt1. In addition, Lpc-EV reverses Aβ-induced downregulation of the Aβ-degrading proteases Matrix metalloproteinase 2 (Mmp-2), Mmp-9, and Neprilysin (Nep), whose upregulation is also controlled by MeCP2 and Sirt1. Lpc-EV treatment restores the downregulated expression of Bdnf, Nt4/5, TrkB, Mmp-2, Mmp-9, and Nep; induces the upregulation of MeCP2 and Sirt1 in the hippocampus; alleviates Aβ accumulation and neuroinflammatory responses in the brain; and mitigates cognitive decline in Tg-APP/PS1 mice. These results suggest that Lpc-EV cargo contains a neuroactive component that upregulates the expression of neurotrophic factors and Aβ-degrading proteases (Mmp-2, Mmp-9, and Nep) through the upregulation of MeCP2 and Sirt1, and ameliorates Aβ pathology and cognitive deficits in Tg-APP/PS1 mice.